Converge, Version 3.0. (1993) - Tadj Tadj, Lotfi Lotfi
Abstract : Although intended for college teachers/students, Converge presents a feature that may interest all scientists: it allows an easy export of graphic files to most known word processors, specifically to the 𝔼 𝕏 ℙ, Version 2.1, a powerful WYSIWYG mathematical word processor.